(untitled) (Pragyaratna प्रज्ञारत्न, 2023)
The integration of technology into education has reshaped traditional teaching methods, especially in the field of economics education. Digital resources and online learning platforms offer novel ways to enhance the learning experience, bridging the gap between theoretical concepts and real-world applications. This systematic review critically examines the impact of technology on economics pedagogy, aiming to uncover both the potential benefits and challenges. However, challenges related to accessibility, equitable technology access, instructor presence, and effective pedagogical strategies persist. Through a meticulous screening, 17 relevant and high-quality research articles were selected from a pool of 358. These articles offer diverse perspectives, exploring e-learning effectiveness, engagement through simulations, flipped classroom approaches, student motivation, digital literacy, and accessibility. Collectively, the studies highlight the potential of digital resources to enhance engagement, learning outcomes, and accessibility while acknowledging the challenges posed by technology disparities and pedagogical design. Ultimately, this systematic review emphasizes the importance of embracing technology in economics education and equipping learners with the skills necessary to navigate the complex economic landscape of the 21st century. Educators, researchers, and policymakers can draw valuable insights from this review to create effective and inclusive technology-enhanced learning environments for economics students.